Mushaf Al-Qur'an Braille Pasca-Standardisasi - Ahmad Jaeni (Lajnah Pentashihan Mushaf Al-Qur'an, 2020)
This writing studies the history of the development of the Braille Mushaf of Indonesia after being standardized and confirmed as the Braille Standard Mushaf through the decree of the Minister of Religious Affairs No. 25, 1984. This important phase becomes the starting point for all those who concerned to make the Braille Standard Mushaf as the only guideline in the publication, correction and use. It is through the historical approach by exploring the information from the sources and existing documents that the study arrives at the conclusion that the dynamics occurred after the determination of the Braille Standard Mushaf is reflected in some phases. The early phase is a transitional phase which described the existence of the Braille Standard Mushaf which had not become fully reference yet at the level of the users. The next phase is the phase of the strengthening which is marked by the birth of the revised edition of the Braille Standard Mushaf and has been used more widely. The phase of the nest strengthening is marked by the revised edition of the Braille Standard Mushaf as the new agreement. Of all those dynamics, the role of the government thus becomes the key.